869 Colorectal Cancer Referral Pathways: Impact of First Months of COVID-19. (12th October 2021) - Spyropoulou, L E; Li, M; Curley, D; Martin, E; Wynn, G; Doulias, T
Abstract: Introduction: Whilst daily living has adapted to the "new normal" during Covid-19, colorectal cancer pathways are yet to be revised to reflect this transformation. Government advice to stay at home, hospital avoidance and reduced healthcare access, may be masking a significant proportion of population at risk. We aim to identify changes in colorectal cancer target pathways. Method: All cancer referrals during the initial Covid-19 period were retrospectively analysed, recording type and date of first clinic and investigation, MDT discussion and decision to treat dates. A comparison was made with referral and treatment data from the same referral period in 2019. Results: 338 referrals were received during March-April 2020, compared to 542 in 2019, indicating a 37.6% decrease. A high proportion of patients were reviewed by telephone clinic (63.4%) rather than face-to-face (23.8%), representing a significant shift in practice. An increasing number of patients were initially investigated by CT(40.2%) instead of endoscopy (37.8%). 51(15.5%) patients were not investigated, with COVID-19 being the commonest reason. 25 patients were diagnosed with colorectal cancer, of which 8(32.0%) breached the investigation and 13(52.0%) the treatment date, both usually postponed due to the pandemic. There was a 66.7% reduction in surgical management compared to 2019. Conclusions: Two-week wait pathways are strained in the era of Covid-19. As the fight against the global pandemic continues, patients are mostly seen virtually and receive non-gold standard investigation. With fewer patient presentations and elective surgeries, it is important to continue colorectal cancer surveillance and timely treatment, considering possible alternative pathways.